Early diagnosis and effective treatment regimens are the keys to tackle antimicrobial resistance in tuberculosis (TB): a report from Euroscicon's international TB Summit 2016 - Maitra, Arundhati; Tengku Mohd. Kamil, Tengku Karmila; Shaik, Monisha; Danquah, Cynthia Amaning; Chrzastek, Alina; Bhakta, Sanjib (Taylor & Francis, 2017)
To say that tuberculosis (TB) has regained a strong foothold in the global human health and wellbeing scenario would be an understatement. Ranking alongside HIV/AIDS as the top reason for mortality due to a single infectious disease, the impact of TB extends far into socio-economic context worldwide. As global efforts led by experts and political bodies converge to mitigate the predicted outcome of growing antimicrobial resistance, the academic community of students, practitioners and researchers have mobilised to develop integrated, inter-disciplinary programmes to bring the plans of the former to fruition. Enabling this crucial requirement for unimpeded dissemination of scientific discovery was the TB Summit 2016, held in London, United Kingdom. This report critically discusses the recent breakthroughs made in diagnostics and treatment while bringing to light the major hurdles in the control of the disease as discussed in the course of the 3-day international event. Conferences and symposia such as these are the breeding grounds for successful local and global collaborations and therefore must be supported to expand the understanding and outreach of basic science research.